A Radiative Chemical Process for the Methylene Blue Degradation by Natural Convective Nanofluid Flow over an Upright Cone - E. Ragulkumar; J. Vinoth Kumar; N. Abirami; P. Sambath; K. K. Viswanathan (The Scientific World Journal)
An upstraight cone with nonisothermal surface velocity, temperature, and concentration was investigated using a numerical solution approach to simulate MHD, MB dye, and various nanofluid flows. Numerical evaluation of the flow field equation was carried out using an excellent finite difference method after it has been converted into a dimensionless form. Different heat transfer occurrences were observed depending on temperature, velocity, and concentration when using several types of nanofluids (TiO, Ag, Cu, and Al2O3Z3). The amount of MB dye that was degraded by the synthesized nanofluids under the influence of sunlight irradiation was 81.40 percent as a catalyst (carbon nanodots). The parametric analysis of various features of flow fields has been shown using graphs. It was observed that heat is generated from the cone during the sun light irradiation reaction, heat is transferred to MB dye containing nanofluids, and heat interacts with nanofluids and is involved in the chemical reaction with the assistance of electrons. As MB dye degrades in the absence of catalysts (carbon nanodots), it is only 52 percent effective. MB dye is degraded at 81.40 percent, then becomes stable, and takes 120 minutes to degrade in nanofluids containing MB dye with catalysts (carbon nanodots).